2001
DOI: 10.1093/carcin/22.8.1239
|View full text |Cite
|
Sign up to set email alerts
|

Site specificity and mechanism of oxidative DNA damage induced by carcinogenic catechol

Abstract: Catechol, a naturally occurring and an important industrial chemical, has been shown to have strong promotion activity and induce glandular stomach tumors in rodents. In addition, catechol is a major metabolite of carcinogenic benzene. To clarify the carcinogenic mechanism of catechol, we investigated DNA damage using human cultured cell lines and 32P-labeled DNA fragments obtained from the human p53 and p16 tumor suppressor genes and the c-Ha-ras-1 proto-oncogene. Catechol increased the amount of 8-oxo-7,8-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 56 publications
7
64
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20] Consistent with this notion, we also detected ROS and Cu(I) in the reaction mixture that caused DNA damage. To clarify the active species responsible for the DNA damage, the effects of ROS scavengers and a Cu(I)-specific chelator were examined.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18][19][20] Consistent with this notion, we also detected ROS and Cu(I) in the reaction mixture that caused DNA damage. To clarify the active species responsible for the DNA damage, the effects of ROS scavengers and a Cu(I)-specific chelator were examined.…”
Section: Discussionsupporting
confidence: 82%
“…Taken together, these results also suggest that Cu(I)-OOH complexes derived from the reaction of hydrogen peroxide with Cu(I) may play a role in causing DNA damage, as proposed by Kawanishi and co-workers. 13) The Cu(I) formed from Cu(II) bound to DNA interacts with hydrogen peroxide, resulting in the formation of DNA-Cu(I)-OOH complexes. Hydroxyl radicals released from these complexes immediately attack adjacent DNA before they can be scavenged by hydroxyl radicals scavengers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the ROS can be produced abundantly through the reduction of the oxidized form, such as semiquinone radical or 1,2-benzoquinone, by NADH non-enzymatically. Collectively, it is concluded that the oxidative DNA damage by catechol through generation of ROS plays an important role in the carcinogenic process of catechol and benzene (24,25).…”
Section: The Role Of Reactive Oxygen Species In Carcinogenesismentioning
confidence: 99%
“…The CL time profiles were apparently different between these structural isomers. It has been reported that p-quinone is reduced to semiquinone radical by singleelectron reduction [31] whereas o-quinone is reduced to quinol by two-electron reduction [29,32] The CL of the biologically important quinones such as ubiquinone, phylloquinone and PQQ was also measured by the proposed CL assay and the intense CLs were observed for these quinones. …”
Section: Propertiesmentioning
confidence: 99%